Talent identification of 12-year old male Australian rules footballers: Physical advantages and prognosis for junior and senior national-level selection. - Paul Larkin; Gyan Wijekulasuriya; Sam Greer (PLoS ONE)
Talent identification focuses on the ability to identify and select young athletes who show potential for future sporting success. The aim of this study was to compare the anthropometry and physical performance of male youth Australian Football players selected and not selected into a high performance sports academy program. Its secondary aim was to determine whether selection into a talent development environment at 12 years old affects the odds of selection into subsequent junior national level representative and senior professional Australian Football programs. 168 youth males (11.7 ± 0.4 years) who nominated for the selection process to attend a specialised high school sports academy completed a series of physical and anthropometric assessments. The data collection period occurred over seven years (2013-2019), with a prognostic period between one to ten years. Results found selected 12 years olds were taller and had greater lower body power, speed and aerobic fitness than non-selected athletes. A combination of height, aerobic fitness, and lower body power best distinguished between selected and non-selected players. This discriminant analysis had high accuracy and greater sensitivity than specificity. Further, athletes selected into the talent development environment had a much greater likelihood of being selected into junior state/national (54-fold) and senior professional (5-fold) teams than non-selected athletes. Overall, the findings demonstrate some support for the prognostic ability of selection into a talent development program at 12 years old to predict later selection in the talent pathway. These findings support the role of talent development programs in the development of male Australian footballers.